Myofibroma of the gingiva – A rare case of diagnostic predicament - Arunima Sarma; Shraddha Jugade; Sunil Surendraprasad Mishra; Trupti Gaikwad; Shrutika Sonawane; Ashutosh S Dighe (Journal of International Clinical Dental Research Organization, 2023)
Myofibroma is a very uncommon benign soft-tissue neoplasm occurring very rarely in the oral cavity with rare occurrence seen in the gingiva. Being a rare entity, the knowledge about microscopic features is important in its diagnosis and treatment planning. We hereby report the case of a 21-year-old male patient diagnosed with myofibroma based on the histopathological and immunohistochemistry analysis such as immunohistochemical antibodies for alpha-smooth muscle actin, CD34, S-100, and desmin.